1989
DOI: 10.3382/ps.0680762
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Deposition and Cellularity in Cimaterol-Treated Female Broilers

Abstract: The effect of feeding a beta agonist, cimaterol, on carcass yield and composition and adipose tissue development was studied in female broilers. Cimaterol was provided at .25 ppm in the feed starting at 4 wk of age. Birds were sacrificed at 4, 6, 8, 10, 12, and 16 wk for determination of eviscerated carcass yield, carcass composition, and growth and cellularity of the abdominal, neck, back, and sartorial adipose depots. Carcass yield was significantly (P less than .01) greater in treated birds than in controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It should be noted that the abdominal adipose tissue weight in the fat chicken line was much heavier as compared with that of other broilers at an equal age or BW (Cartwright et al, 1986;Cartwright, 1991). According to the data from Merkley and Cartwright, the abdominal fat pad weight of our fat birds at 7 wk of age was approximately equal to that of 12-wk-old broilers of the reported population (Merkley and Cartwright, 1989). For this reason, the difference in cell hypertrophy between our fat broilers and other broilers may be explained primarily by the sustained selection pressure on fatness traits, which has led to a high fat storage capacity and the acquisition of a "critical fat cell size" at a younger age (Marques et al, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…It should be noted that the abdominal adipose tissue weight in the fat chicken line was much heavier as compared with that of other broilers at an equal age or BW (Cartwright et al, 1986;Cartwright, 1991). According to the data from Merkley and Cartwright, the abdominal fat pad weight of our fat birds at 7 wk of age was approximately equal to that of 12-wk-old broilers of the reported population (Merkley and Cartwright, 1989). For this reason, the difference in cell hypertrophy between our fat broilers and other broilers may be explained primarily by the sustained selection pressure on fatness traits, which has led to a high fat storage capacity and the acquisition of a "critical fat cell size" at a younger age (Marques et al, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…The discrepancy between the results of Foglia et al (1994) and our results may result from our use of samples from multiple regions of subcutaneous adipose tissue rather than from a single specific location. Merkley and Cartwright (1989) also give another explanation for this phenomenon; their study suggests that there are many regionspecific differences in the white adipose tissue growth rate. Adipose tissue growth is accompanied by the development of the connective tissue matrix and blood vessels.…”
mentioning
confidence: 92%
“…A sample of approximately 100 mg from the abdominal fat pad of each of 10 birds from each experimental group was weighed and fixed in osmium tetroxide for determination of adipocyte size and number (Cartwright et ai, 1986;Cartwright, 1987). Carcass moisture, protein, fat, and ash were obtained after the whole carcass was ground with an equal weight of water in a Waring blender (Fisher Scientific, Fairlawn, NJ) as previously described for broilers (Merkley and Cartwright, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Dean and Dalrymple (1988) reported that cimaterol while decreasing live weight increased the yield of breast and leg muscle in Peking ducks at 44 days of age. However, other studies suggest that beta adrenergic agents are not as effective in poultry as in larger meat producing animals (Hanrahan et al, 1986;Merkley and Cartwright, 1989). Whether beta agonists have a greater effect on lipid deposition through decreases in lipogenesis or increases in lipolysis has not been determined.…”
Section: Introductionmentioning
confidence: 94%